Transformation of Modern Agriculture through Agricultural Mechanization in Indonesia - Ahmad, Ahfandi; Sulaiman, Andi Amran; Tarman, Risma Niswati; Patanduk, James WT (Tarjih : Agribusiness Development Journal, 2025)
Agricultural mechanization is one of the important components for modern agriculture in achieving sustainable food self-sufficiency targets. In fact, advances in mechanization technology will make agriculture triumphant, so that Indonesia as the world's food barn can be realized.  This study aims to see how the development of innovation-based agricultural mechanization, as well as how the efficiency of agricultural products in the application of agricultural mechanization. The government through the Ministry of Agriculture has created many works to build mechanization 4.0, including (1) rice seed spreading drones, (2) rice planting robots, (3) autonomous tractors, and (4) integrated harvesting plus tillage machines. These four agricultural machines can be a solution for Indonesian farmers in running a modern farming business. The government, through the Ministry of Agriculture, has distributed agricultural machinery assistance in an effort to help farmers.  The use of rice transplanter (transplanting machinery) can save 30 percent of planting costs compared to conventional planting methods. Nationally, the cost of planting that can be saved reaches Rp 8.6 trillion every year. Weeding tools, the use of weeding machines is three times faster than conventional methods with a savings value of Rp 7 trillion in weeding costs. The use of tractors for soil cultivation can also reduce the use of conventional labor with faster operationalization.  The use of agricultural machinery, both pre- and post-harvest, is a driving force for accelerating the process of increasing production and farming efficiency so that farmers get greater benefits.